Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4162/nrp.2022.16.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laxative effects of fermented soybeans (Cheonggukjang) containing toxins and biogenic amines against loperamide-induced constipation mouse model

Abstract: BACKGROUND/OBJECTIVES Cheonggukjang is a traditional fermented soybean paste with significant health-promoting effects. On the other hand, there have been insufficient studies on the safety and efficacy of Cheonggukjang , which is produced using traditional methods containing toxins and biogenic amines (BAs). This study compared the laxative effect of Cheonggukjang , containing high or low levels of toxins and BAs (HTBC or LTBC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…32 An earlier study found that Cheonggukjang , another traditional Korean soybean fermented food, elicits anti-constipation effects by downregulating MAPK signaling pathways in LOP-induced constipation mice. 46 Consistently, the present study found that BMG and VMG suppressed MAPK signaling pathways in LOP-induced constipation mice. Isoflavones, such as daidzein, have anti-inflammation effects through MAPK signaling pathway modulation, 47 and the main ingredient in Gochujang is soybean.…”
Section: Discussionsupporting
confidence: 87%
“…32 An earlier study found that Cheonggukjang , another traditional Korean soybean fermented food, elicits anti-constipation effects by downregulating MAPK signaling pathways in LOP-induced constipation mice. 46 Consistently, the present study found that BMG and VMG suppressed MAPK signaling pathways in LOP-induced constipation mice. Isoflavones, such as daidzein, have anti-inflammation effects through MAPK signaling pathway modulation, 47 and the main ingredient in Gochujang is soybean.…”
Section: Discussionsupporting
confidence: 87%
“…The content of biogenic amines and aflatoxins in the GJ samples was analyzed using high-performance liquid chromatography (Agilent 1200 series) as described previously [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The murine macrophage-like cell line RAW264.7 was obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured as previously described (Kim et al 2022). In brief, the cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen, Carlsbad, CA, USA) with 10% heat-inactivated fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA, USA) and penicillin/streptomycin (100 U/mL) (Invitrogen, Carlsbad, CA, USA) at 37 °C under a humidified atmosphere containing 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…Whole-cell lysates of the cultured cells were obtained and separated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and Western blot analysis was performed as described previously (Kim et al 2022). The primary and secondary antibodies used in Western blot analyses were purchased from Cell Signaling Technology Inc. (Beverly, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%